The Effect of Marketing Mix Towards Decision of Muslim Consumers in Travelug - Luqmanul Hakiem Ajuna (Jurnal Ilmiah Ekonomi Islam, 2020)
This research aims to find out to what extent and how the influences of marketing mix toward decision of Muslim consumers in using Travelug travel agency service. Based on data analysis using double linear regression from 92 respondents with accidental random sampling, it is found that marketing mix affects Muslim consumers in using Travelug service as much as 26,1%, while other 73.9% is affected by variables out of this research.